1953
DOI: 10.1063/1.1721421
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wave Propagation over a Coated Conductor with Small Cylindrical Curvature in Direction of Travel

Abstract: Propagation of surface waves over an undulating bed Phys. Fluids A 1, 1898 (1989); 10.1063/1.857515 Nonlinear surface−wave propagation over plasmas and conductors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, the first attempt to study surface wave propagation over a coated conductor with small cylindrical curvature in the direction of propagation was reported by Horiuchi (1953) from the Laboratory of Communication Instruments, Tokyo, Japan. The outline of how to study the wave fields in this case was suggested on the basis of the system of plane conductors studied earlier.…”
Section: Introductionmentioning
confidence: 99%
“…However, the first attempt to study surface wave propagation over a coated conductor with small cylindrical curvature in the direction of propagation was reported by Horiuchi (1953) from the Laboratory of Communication Instruments, Tokyo, Japan. The outline of how to study the wave fields in this case was suggested on the basis of the system of plane conductors studied earlier.…”
Section: Introductionmentioning
confidence: 99%